The Assessment of the Efficiency of Classical and co-Operative Training in Promoting The Participation of Employees of R .P.C in the Field of H.S.E - Hassan, Elham Mubarak; Varshosaz, Katayoon (European Journal of Sustainable Development, 2016)
This study aims to evaluate the performance and efficacy of co-operative and classical learning. The study investigates changes in knowledge, attitude, practice and skill of factory workers of RAZI Petrochemical in the field of HSE in 2015. The statistical population in this study is all personnel of RAZI Petrochemical Company. A sample size of 80 persons were selected for evaluation of assumptions. The sample size was divided into two groups of test and control (40 in test group and 40 in control group) both accidentally for. A questionnaire consisting of four parts, knowledge, attitudes, skills and practice was used to collect data in this survey .The reliability of each part was 0.86, 0.72, 0.89 and 0.68 respectively. The questionnaires were distributed among test and control groups before training. Then the test and control groups were individually exposed to cooperative and classical training. After a week and then after a month dependent variables were evaluated in test and control groups. The results showed that training in either classic or cooperative method, increases knowledge and attitudes of employees .Knowledge and attitudes before training was similar in both groups (P> 0.05). After training, the level of knowledge in cooperative method, in a week and a month after training was significantly higher than the classical method (P <0.05).While in cooperative training group the increasing trend of attitude of personnel was maintained, in classical training group attitude of personnel, a week and a month after training did not change significantly (P>0.05). The results of evaluation of skill and performance of employees in classical training group a week and a month after training to before training did not change significantly (P> 0.05).But The results of evaluation of skill and performance of employees in cooperative training group a week and a month after training to before training changed significantly (P <0.05). It seems that classical training method has no effect on increasing the performance and skill of employees while cooperative method had significant effect (P <0.05). Finally, to improve and upgrade within the HSE, a review of the existing guidelines and using experiences of peers and leading international companies and high-quality uninterrupted training in this field is recommended. Key words: Classical Training, Cooperative Training, BASNEF Method, Hygiene, Safety and the Environment, RAZI Petrochemical